Triple combination of carbosilane dendrimers, tenofovir and maraviroc as potential microbicide to prevent HIV-1 sexual transmission. (March 2015) - Sepúlveda-Crespo, Daniel; Sánchez-Rodríguez, Javier; Serramía, María Jesús; Gómez, Rafael; De La Mata, Francisco Javier; Jiménez, José Luis; Muñoz-Fernández, Mª Ángeles
Aim: To research the synergistic activity by triple combinations of carbosilane dendrimers with tenofovir and maraviroc as topical microbicide.Methods: Cytotoxicity, anti-HIV-1 activity, vaginal irritation and histological analysis of triple combinations were determined. Analysis of combined effects and the median effective concentration were performed using CalcuSyn software.Results: Combinations showed a greater broad-spectrum anti-HIV-1 activity than the single-drug, and preserved this activity in acid environment or seminal fluid. The strongest combinations were G2-STE16/G2-S24P/tenofovir, G2-STE16/G2-S16/maraviroc and G2-STE16/tenofovir/maraviroc at 2:2:1, 10:10:1 10:5:1 ratios, respectively. They demonstrated strong synergistic activity profile due to the weighted average combination indices varied between 0.06 and 0.38. No irritation was detected in female BALB/c mice.Conclusion: The three-drug combination increases their antiviral potency and act synergistically as potential microbicide.